SURVEI KETERAMPILAN SERVIS FOREHAND TENIS MEJA SISWA KELAS X SMA - Aryanti, Desti; Decheline, Grafitte; Kurniawan, Alexander (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Problems: It was found that students' forehand serve skills were still suboptimal. Many students failed to apply the technique correctly and appeared to be careless in their execution. Purpose: This study aims to determine and assess the skill level of class X high school students in performing table tennis forehand serves. Methods: This research uses a quantitative descriptive method with the object of study being the forehand service skills of high school students in table tennis. Results Based on the results of the Table Tennis Forehand Service Test Assessment, researchers obtained survey results that were divided into 3 categories, namely: 3 students had average skills, 9 students had good skills, and 18 students had very good skills. Conclusion: The survey results show that the forehand serve skills of class X high school students in table tennis are in the very good category. Mastery of the forehand serve skill technique is very important in table tennis where the serve is a start in a game, success in a game depends on the start made and the forehand serve can be used as an initial attack in a game that can produce a point if done with the right technique.